Большой баклан (Phalacrocorax carbo) в Каневском заповеднике - Грищенко, В.Н.; Яблоновская-Грищенко, Е.Д. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2008)
The Kaniv Nature Reserve is situated in the Middle Dnieper area near the town of Kaniv. Cormorant (Phalacrocorax carbo) nests on the Kruglik Island, in a mixed colony with Grey Heron (Ardea cinerea). For the first time 11 Cormorant pairs have nested in 1999. Their number rapidly increased. In 2008 already 625 occupied nests of the Cormorants were recorded. Number of herons has not decreased yet.
The Cormorants arrive in spring to their breeding area very early and migrate to the wintering places in autumn very late. Average date of the spring arrival in 1999-2008 is 9.03, average date of the autumn departure - 11.11. Some cases of Cormorant's wintering in the Dnieper area were observed.